High-entropy alloys: Electrochemical Nanoarchitectonics toward high-performance Water splitting - Christian Iffelsberger; Katarina A. Novčić; Eva Kolíbalová; Frank-Michael Matysik; Martin Pumera (Electrochemistry Communications)
High-entropy alloys (HEAs) offer unprecedented catalytic properties over single-composition nanoparticles or single atom engineered materials. Traditionally, the Hume–Rothery rule suggests that only size-and-structure similar elements can be mixed in conventional alloying, which limits the possible combinations of alloying elements. Here we propose an electrochemical approach as an innovative and alternative synthetic method for preparation of HEAs. Upon an electric arch by applying voltage drop of about 2 MV/m with high current densities and using ultra-thin Pt wire in glass, whose movement, in the aqueous solution containing the salt of the elements to be incorporated to the HEAs, is controlled by the scanning electrochemical microscope (SECM), the HEAs, consisting of doped silica nanobeads are produced. The composition of such HEAs depends on the materials and solution used in their preparation and thus it contains Pt, Si, Al, Ca, K, Cl, Mn, Zn, Na, N, Mo, and S. This new approach is compatible with ambient air and aqueous solution processes and is not limited by material selection, presenting a significant advancement in the synthesis of functional nanomaterials. The findings underline the potential of these high-entropy nanostructured materials in advancing the efficiency of industrial processes, particularly in the realm of green hydrogen production through water splitting. This simple, low-voltage, room temperature process is suitable for fabrication of HEAs of various composition and has the applicability to wide spectra of catalytic reactions.